Democracy's think tank : the Institute for Policy Studies and progressive foreign policy - Mueller, Brian S. (Brian Scott), 1983- (University of Pennsylvania Press, 2021)
"This book is an institutional history of the Institute for Policy Studies, one of the first Washington, DC, think tanks and a model for other think tanks. The founders intended IPS to be a clearinghouse of information for activists outside DC that would help them do their work"--